Shooting efficiency and structure of shooting in 3×3 basketball compared to 5v5 basketball - Erculj, F.; Vidic, M.; Leskošek, B. (International Journal of Sports Science & Coaching, 2020)
This article presents and analyses certain playing characteristics of men's and women's 3 × 3 basketball in relation to shooting at the basket. Our intention was to compare this young and developing basketball discipline with the more established and traditional 5v5 basketball. For this purpose, over 400 matches were analysed in the U18 age category during the men`s and women`s European Championship (5v5 Basketball) and the Youth Olympic Games (3 × 3 Basketball). The research confirms some differences in the efficiency and structure of shooting. It can generally be said that male and female 3 × 3 basketball players take more long-distance shots (behind the 6.75 m line) and take fewer free throws than their counterparts in 5v5 basketball. When shooting from behind the 6.75 m line, both male and female 3 × 3 basketball players are less efficient than their 5v5 basketball counterparts, and similar applies to free throws. The reasons for these differences may entail many factors, including differences in the game rules, the playing conditions on outdoor courts, different technical and tactical requirements and the characteristics (style) of playing as well as the quality and performance level of basketball players.